The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1523/jneurosci.2110-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Disease Progression-Dependent Effects of TREM2 Deficiency in a Mouse Model of Alzheimer's Disease

Abstract: Neuroinflammation is an important contributor to Alzheimer's disease (AD) pathogenesis, as underscored by the recent identification of immune-related genetic risk factors for AD, including coding variants in the gene TREM2 (triggering receptor expressed on myeloid cells 2). Understanding TREM2 function promises to provide important insights into how neuroinflammation contributes to AD pathology. However, studies so far have produced seemingly conflicting results, with reports that amyloid pathology can be both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
268
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(312 citation statements)
references
References 38 publications
12
268
3
Order By: Relevance
“…Plaque accumulation is exacerbated at later ages in a TREM2 knockout AD mouse model (17). In AD patients, Aβ plaques appear a decade or two before clinical symptoms of AD (18).…”
Section: Resultsmentioning
confidence: 99%
“…Plaque accumulation is exacerbated at later ages in a TREM2 knockout AD mouse model (17). In AD patients, Aβ plaques appear a decade or two before clinical symptoms of AD (18).…”
Section: Resultsmentioning
confidence: 99%
“…A recent report indicated that the opposing results from previous work might reflect a disease progression-dependent influence of TREM2 deficiency on AD pathology. While TREM2 deficiency in young APP/PS1-21 mice ameliorated amyloid pathology, it enhanced amyloid deposition at later disease stages (157). Additionally, TREM2 deficiency in aged mice decreased plaque-associated myeloid cell accumulation by reducing proliferation (157).…”
Section: Trem2mentioning
confidence: 99%
“…While TREM2 deficiency in young APP/PS1-21 mice ameliorated amyloid pathology, it enhanced amyloid deposition at later disease stages (157). Additionally, TREM2 deficiency in aged mice decreased plaque-associated myeloid cell accumulation by reducing proliferation (157). Considering the dual role of TREM2, a longitudinal assessment of TREM2 in conditional knockout models will reveal important effects of TREM2 signaling on myeloid cells during AD progression to support development of TREM2-directed therapeutics for different disease stages.…”
Section: Trem2mentioning
confidence: 99%
“…A major difference between these two studies, other than the animal models, was the age at which the animals were analyzed -8.5 months in the [ 5 3 0 _ T D $ D I F F ] 5ÂFAD and 4 months in the APPPS1 experiments. A recent study attempted to reconcile these results by looking at the cortex of APPPS1 mice at different ages, reporting that plaque pathology was decreased at 2 months of age, but increased at 8 months of age, in Trem2-deficient mice [142]. This may imply that the effects of TREM2 activity at early or late stages of disease could be detrimental or beneficial, respectively.…”
Section: Trem2 In the Developing And Aging Brainmentioning
confidence: 99%